Terapi Bekam dan Akupunktur Terhadap Penurunan Tekanan Darah pada Penderita Hipertensi Primer (Esensial) di Klinik Herbal El Zahra Kota Tarakan - Yumira Ria Santi; Yhona Paratmanitya; Pratiwi Pratiwi (Alma Ata University Press, 2014)
Hypertension is health problems are often happens in society, both of urban and rural community. Prevalence in Indonesia reached was 75.8% quite high, the long term medical treatment make it more difficult to handled properly. Alternative treatment like cupping and acupuncture are patients hypertension efforts to be free from side effects inflicted by chemical medicines. The purpose of this study was to determine the effect of cupping and acupuncture therapy effectiveness in blood pressure reduction among patients with primary hypertension. Study design used in this study was pre experimental designs with pretest–posttest, used statistics of paired t-test and independent t-test. The Results of paired test showed that value of p were 0.003 for systole blood pressure of cupping and 0.000 for systole blood pressure of acupuncture while diastole blood pressure of cupping obtained by value of p were 0.065 and 0.775 for diastole blood pressure of acupuncture, it means that cupping and acupuncture only had an affect on systole blood pressure reduction. Analysis results of independent t-test showed that value of p were 0.051 for systole blood pressure and 0.511 for diastole blood pressure, it means that there was no differences between cupping and acupuncture therapy. Based on average of blood pleasure reduction, acupuncture can reduce of 17 mmHg of systole blood pressure while cupping only 10 mmHg, in acupuncture also reduce of 16 mmHg diastole blood pressure while cupping canl 19 mmHg.